2019
DOI: 10.1155/2019/1625837
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Chronic Kidney Disease in a Semiurban Community in Lagos

Abstract: Background and Objectives. The prevalence of noncommunicable diseases like chronic kidney disease is on the rise in third-world countries. In Nigeria and most sub-Saharan African countries, there is dearth of community-based studies on prevalence and predictors of chronic kidney disease, prompting us to undertake this study. Materials and Methods. This was a cross-sectional study, aimed at ascertaining the prevalence and predictors of chronic kidney disease (CKD) in a semiurban community in Lagos, Southwest Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
3
10
0
1
Order By: Relevance
“…The prevalence of CKD and reduced renal function were much higher in the females compared with the males. This finding was similar to the results from several other cross-sectional studies [17,42,43]. Several possible explanations of this phenomenon are as follows: (a) Obesity and central obesity may play an indirect role in mediating the pathophysiological development [43].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence of CKD and reduced renal function were much higher in the females compared with the males. This finding was similar to the results from several other cross-sectional studies [17,42,43]. Several possible explanations of this phenomenon are as follows: (a) Obesity and central obesity may play an indirect role in mediating the pathophysiological development [43].…”
Section: Discussionsupporting
confidence: 89%
“…Several possible explanations of this phenomenon are as follows: (a) Obesity and central obesity may play an indirect role in mediating the pathophysiological development [43]. The prevalence of obesity and central obesity were significantly higher in female (32.3% and 74%, respectively) compared with the male (16.9% and 33.1%, respectively) in this study, which was consistent with the finding of Yu’s [44]; (b) the differences in physiological structure (e.g., glomerular structure and muscle mass) and hormone metabolism between men and women may partly explain this phenomenon [42]; (c) data from the Chinese National Renal Data System (CNRDS) showed that there were more male end-stage renal disease patients with hemodialysis (ESRD-HD) patients than female patients (1.5:1, respectively), and the incidence of ESRD-HD patients obtaining HD was higher in males than in the female population [45]. The result suggested that the access to medical care was substantially limited for women, which might partly explain a higher prevalence of CKD in the females.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the risk of abnormal kidney function was also twice as high in women as in men. Similar observations were also made in several other studies [ 7 , 31 , 32 ]. This could be explained by our study population, which is more female, and by the average age of the participants with abnormal kidney function, which is relatively high in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with CKD have a high risk of progression to end-stage renal disease (ESRD). The end-stage of this disease requires dialysis or kidney transplantation [ 7 ]. Although more than 2 million people worldwide need chronic kidney replacement therapy, only a minority of patients who have elevated risks of developing ESRD receive medical care [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a global public health problem (1,2), that increasing rapidly worldwide and is gaining much attention in both the developed as well as developing countries (3,4). It is found in 10% of the global population (5,6), and it affects 10-16% of the adult population in China, Asia, Australia, Europe and the United States (7).…”
Section: Introductionmentioning
confidence: 99%